Extended-Spectrum Beta-Lactamase-producing Escherichia coli isolates in feline fecal samples - Rodríguez-Duran, Norma Alelia; Sánchez-Prado, Raquel Estefanía; Pérez-Rodríguez, Jhonny Edgar; Lascano-Domínguez, Brandon Joao; Luna-Florin, Johon Armando; Guerrero-Lopez, Ana Elizabeth; Guzmán-Pucha, Samantha; Sánchez-Prado, Robert Gustavo (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Extended-spectrum beta-lactamases (ESBLs) are bacterial enzymes that confer resistance to beta-lactam antibiotics, such as penicillins and cephalosporins of various generations, with the exception of cephamycins and carbapenems. These enzymes can be inhibited by clavulanic acid. Although initially associated with Klebsiella pneumoniae, Escherichia coli is now one of the main ESBL producers in both hospital and community environments. ESBL-producing E. coli strains are classified as priority pathogens by the World Health Organization (WHO) due to their ability to develop resistance to multiple antibiotics (MDR). This phenomenon is driven by gene transmission via plasmids, which facilitates their spread between humans and animals. Close contact between humans and domestic dogs is a potential risk factor for the dissemination of these multidrug-resistant strains. Globally, it is estimated that around 6,9% of dogs carry ESBL-producing E. coli, while in Ecuador, some studies have reported the presence of ESBL-producing E. coli in up to 40% of fecal samples from canines. This study focused on evaluating the prevalence of ESBL-producing E. coli strains in 114 dogs treated at the Veterinary Clinic of the University of Machala. Samples were collected via rectal swabs and cultured on chromogenic agar, which allowed for the identification of 39 ESBL-producing E. coli strains, representing 34,2% of the total. These strains exhibited high resistance to monobactams, cephalosporins, and tetracyclines, although all were sensitive to carbapenems such as imipenem and meropenem. These findings highlight the need for increased surveillance of antimicrobial resistance in domestic animals, as the indiscriminate use of antibiotics in veterinary medicine may be contributing to the selection of resistant strains, with significant implications for public health.